1992
DOI: 10.1209/0295-5075/20/5/014
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Fluctuations, Negative Hall Effect, and Thermally Activated Resistivity in Layered and Thin-Film Superconductors in an External Magnetic Field

Abstract: The thermally activated resistivity, r,, and the negative Hall resistivity, ry are explained as two consequences of the same effect, namely the unbinding of vortex pairs m the vicinity of T,. Both r, and rw exhibit a thermally activated behaviour. The activation energy depends logarithmically on the magnetic field. Our explanation suggests rwrh with a = 1 in accordance with recent measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 23 publications
4
18
0
2
Order By: Relevance
“…Theoretically, this variation of T 0 is consistent with the collective pinning model of vortex transport 22,34,36 . This type of logarithmic field dependence of activation energy is also found in several other cases, such as thermally activated motion of vortex-antivortex pairs 37 or activation over surface barrier associated with edge pinning 38 . To show the dependence of R on the width of the nanowires we present in Figure 6, R (w) for different ( B Bc ) values measured at 0.2 K. In the superconducting side of the SIT, R decreases as w is increased, whereas, in the insulating side, R increases with w. A log-log representation is used to include the film's data for the same ( B Bc ) values as of the wires.…”
Section: Resultssupporting
confidence: 68%
“…Theoretically, this variation of T 0 is consistent with the collective pinning model of vortex transport 22,34,36 . This type of logarithmic field dependence of activation energy is also found in several other cases, such as thermally activated motion of vortex-antivortex pairs 37 or activation over surface barrier associated with edge pinning 38 . To show the dependence of R on the width of the nanowires we present in Figure 6, R (w) for different ( B Bc ) values measured at 0.2 K. In the superconducting side of the SIT, R decreases as w is increased, whereas, in the insulating side, R increases with w. A log-log representation is used to include the film's data for the same ( B Bc ) values as of the wires.…”
Section: Resultssupporting
confidence: 68%
“…Several theoretical approaches have attempted to explain this phenomenon, but no agreement has been achieved. The questions, whether the Hall anomaly is an intrinsic electronic property, determined by the trajectory of an individual vortex [1][2][3][4] if collective vortex phenomena are essential [5,6], or if vortex pinning is indispensable for the sign reversal [7,8], are currently not resolved. Other models are based on the general grounds of the time-dependent Ginzburg-Landau theory [9][10][11][12], but one needs a microscopic theory to predict the sign of the vortex Hall effect.…”
mentioning
confidence: 99%
“…Several theories were suggested to explain this behavior. They took into account particle hole asymmetry [4,5], the presence of antivortices [6,7] or vacancies in a pinned vortex lattice [8]. Wang et al [9] developed a theory explaining observed results by pinning and thermal fluctuation effects.…”
Section: Introductionmentioning
confidence: 99%